2020
DOI: 10.1080/10508422.2020.1837136
|View full text |Cite
|
Sign up to set email alerts
|

Basic values predict unethical behavior in sport: the case of athletes’ doping likelihood

Abstract: Although basic values have been linked with unethical attitudes and behavior in non-sport contexts, their association with doping in sport has yet to be established. We examined the relationships between basic values and doping likelihood. College athletes (N = 233, 61% females) rated the importance of basic values using the Portrait Values Questionnaire Revised and indicated their likelihood of doping in a hypothetical scenario. In terms of basic value dimensions, self-enhancement and conservation values were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Recently, it has been shown that athletes’ perceptions of the importance of clean sport and clean sport values can vary across different countries ( Woolway et al, 2021 ). As values are linked to doping behaviour ( Ring et al, 2020 ), it could be that culture may also play a role in engagement with, and acceptance of whistleblowing in sport ( Keenan, 2007 ; Bondarev et al, 2021 ). Culture refers to the individual’s characteristics that based on the perception of rules, norms, roles, and values, influenced by various societal levels (e.g., country, race, occupation etc.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that athletes’ perceptions of the importance of clean sport and clean sport values can vary across different countries ( Woolway et al, 2021 ). As values are linked to doping behaviour ( Ring et al, 2020 ), it could be that culture may also play a role in engagement with, and acceptance of whistleblowing in sport ( Keenan, 2007 ; Bondarev et al, 2021 ). Culture refers to the individual’s characteristics that based on the perception of rules, norms, roles, and values, influenced by various societal levels (e.g., country, race, occupation etc.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it is not enough to limit oneself to sport-related values or to emphasize their importance in sport alone, especially in strengthening moral identity. Ring et al [ 54 ] examined the relationships between Schwartz’s basic values and doping likelihood among university athletes and found that self-enhancement values were positively related, whereas self-transcendence and conservation values were negatively related, to doping likelihood. Therefore, in order to strengthen the moral identity of athletes and promote more negative attitudes to doping in sport, coaches need to not only encourage athletes to analyze situations related to both doping specifically and anti-social behavior in general.…”
Section: Discussionmentioning
confidence: 99%
“…The measure has demonstrated strong relationships to other doping risk factors (e.g. doping moral disengagement and doping self-regulatory efficacy; Ring, Kavussanu, Lucidi, et al, 2019a) and has shown very good internal consistency (α = 0.93; Ring et al, 2020).…”
Section: Doping Likelihoodmentioning
confidence: 99%
“…A body of research has assessed an athlete's likelihood to dope (e.g. Connor et al, 2013; Kavussanu et al, 2020; Ring et al, 2020). Research has identified strong relationships between doping likelihood and anticipated guilt (Ring, Kavussanu, & Mazanov, 2019b), moral identity (Kavussanu & Ring, 2017; Kavussanu et al, 2020) and moral disengagement (Kavussanu & Ring, 2017; Ring & Hurst, 2019).…”
Section: Introductionmentioning
confidence: 99%